2012
DOI: 10.1002/cjce.21627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diethanolamine and triethanolamine on the properties of electroplated Zn–Ni alloy coatings from acid bath

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Eliaz et al (2010) studied that ZnNi coating showed higher thickness, nickel content, hardness and corrosion resistance with increase in current density up to 4 A dm -2 . Hammami et al (2013) studied the effect of diethanolamine (DEA) and triethanolamine (TEA) on ZnNi alloy coating from an acid bath. The ZnNi coating obtained was fine grain, corrosion resistant and contains Zn and γ-phases.…”
Section: Introductionmentioning
confidence: 99%
“…Eliaz et al (2010) studied that ZnNi coating showed higher thickness, nickel content, hardness and corrosion resistance with increase in current density up to 4 A dm -2 . Hammami et al (2013) studied the effect of diethanolamine (DEA) and triethanolamine (TEA) on ZnNi alloy coating from an acid bath. The ZnNi coating obtained was fine grain, corrosion resistant and contains Zn and γ-phases.…”
Section: Introductionmentioning
confidence: 99%
“…C Pc and R Pc were capacitance and resistance of the corrosion products from the dissolution of Zn coating at a low-frequency. 33 The CPE (Y À Q(u)) impedance is given by eqn (2):…”
Section: Corrosion Resistance Properties Of the Apc-simentioning
confidence: 99%
“…Additives are commonly employed in both electrodeposition and ELD to alter the physical and mechanical properties of deposits such as the grain size, brightness, electrical resistivity, hardness, and smoothness. ,,, Examples include bis-(3-sulfopropyl)-disulfide, , 2-aminobenzothiazole, benzotriazole, polyethylene glycol, ,,, dipyridyls, , saccharin, adenine, ,, guanine, ,, and 3-mercapto-1-propanesulfonate. , Additionally, additives can accelerate or inhibit the rate of deposition. ,,,, There have been very few systematic studies of the effect of additive structure on the film deposition rate or properties. Kondo and co-workers , have demonstrated that for the tertiary amines, nitriloacetic acid (NTA), triethanolamine (TEOA), and triisopropanolamine, there were large differences in the rate of copper ELD using the reducing agent formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanolamines combine the properties of amines and alcohols and therefore have a variety of industrial applications as lubricants, surfactants, and herbicides and in gas purification. , They are versatile ligands that behave as N and O donors and easily form complexes with transition metals. , In ELD and electroplating, ethanolamines have been reported to act as both complexing agents and buffers. ,,,,, A number of studies have reported that TEOA increases the rate of copper deposition which has been attributed to the formation of Cu­(II)–TEOA complexes or mixed ligand species (in the presence of other complexing agents). ,,,, TEOA can also slow the metal deposition rate by adsorbing onto the sample, which inhibits the oxidation of reducing agents, such as formaldehyde. , The properties of the deposited film are also altered by TEOA; the grain size is observed to decrease while the electrical resistivity is improved . There have been far fewer studies of the effect of ethanolamine (EOA) or diethanolamine (DEOA) on ELD and electroplating. , Hammami and co-workers observed differences in the morphologies of electroplated Zn–Ni films using DEOA and TEOA. Using DEOA, the films had a nodular morphology with agglomeration of grains, while the Zn–Ni deposit was composed of triangular-based pyramidal grains when TEOA was employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation